ANALISIS KUALITAS WEBSITE UNIVERSITAS SEBAGAI MEDIA INFORMASI DENGAN METODE WEBQUAL 4.0 - Miftahul Huda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
A university website is a website dedicated to providing information services to the academic community at large and to the general public. The importance of the university website as an information provider should be assessed and adjusted to ensure that the website offers many benefits. The evaluation process uses the WebQual 4.0 model with three dimensions as independent variables: website quality, usability, information quality, and service interaction quality, and user satisfaction as the dependent variable. The subject of this research is the Putra Bangsa University website. The sampling technique used a simple random sampling technique. This study used questionnaire-based primary data with 29 question items and 95 respondents. It received a 78.82% rating in user testing for usability. In terms of information quality, it received a rating of 79.36%. The quality of service interactions received a rating of 78.38%. It has a user satisfaction rating of 79.55%. This put the Putra Bangsa University website in the very user-friendly system category. The results of the hypothesis building analysis as a whole are accepted. The independent variables usability, information quality, and service interaction quality are correlated and closely related to user satisfaction as the dependent variable.